An Existence Result of Positive Solutions for Fully Second-Order Boundary Value Problems - Yongxiang Li; Yaya Shang (Journal of Function Spaces)
An existence result of positive solutions is obtained for the fully second-order boundary value problem  -u′′(t)=f(t,u(t),u′(t)),  t∈[0,1],  u(0)=u(1)=0, where f:[0,1]×R+×R→R is continuous. The nonlinearity f(t,x,y) may be sign-changing and superlinear growth on x and y. Our discussion is based on the method of lower and upper solution.